THE LINGUISTIC LANDSCAPE OF TOURIST AREAS IN MEDAN - Fathul Jannah Harahap; Mulyadi; Tasnim Lubis (Leksema: Jurnal Bahasa dan Sastra, 2025)
This study examines the linguistic landscape of tourist areas in Medan, focusing on how languages operate and function within public spaces. Tourism areas were chosen as the research context because they attract visitors from various backgrounds and often display multilingual practices. This study aims to describe the forms and functions of linguistic landscapes while also exploring the symbolic meanings conveyed through visual elements such as typography, colors, and logos. A qualitative descriptive method was applied, with data collected through observation, interview, and photographic documentation of signs in several tourist destinations, including Istana Maimoon, Masjid Raya Al-Mashun, Tjong A Fie Mansion, Museum Perkebunan I, Shri Mariamman Temple, and the Rahmat International Wildlife Museum. The findings reveal the presence of monolingual, bilingual, and multilingual signs that highlight Medan’s multicultural identity and its role as a domestic and international tourist destination. Indonesian dominates as the national language, reinforcing unity, accessibility, and loyalty to the national language, while foreign languages such as English, Tamil, and Mandarin expand communicative reach. Latin, used in the Rahmat International Wildlife Museum, serves as a scientific language for naming species, emphasizing its educational and academic role. Symbolic functions are conveyed through colors, typography, and logos that embody religious, cultural, and ecological values. Informational functions are realized in name signs, directional signs, informational signs and prohibition signs that guide and regulate visitor behavior. The linguistic landscape of Medan’s tourist areas serves not only as a means of public communication but also as a reflection of cultural heritage, social values, and urban identity.